UJI DAYA HAMBAT EKSTRAK DAUN KAYU MANIS (Cinnamomum burmanii) TERHADAP BAKTERI Aeromonas hydrophila - Safratilofa Safratilofa (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Aeromonas hydrophila is one of the pathogens cause disease incidence of Motile Aeromonad Septicaemia (MAS) on fish farming. Efforts are being made to cope with the disease by administering antibiotics. Administering of antibiotics continuously can cause pollution to the environment, resistance in bacteria and residues in fish. The use of bio-pharmacy performed as an alternative antibakterial that are natural and effective in inhibiting bacterial growth and eco-friendly, one crop of cinnamon (Cinnamomum burmanii). This research aims to know the effectiveness of cinnamon leaf extract c. burmanii antibacterials in inhibiting the growth of bacteria Aeromonas hydrophila.This research is experimental research laboratories. Antibacterial test done by the method of macrodilution. Cinnamon leaf extract dose the word i.e. 0%, 0.25%, 0.5% and 1%. The results showed a dose of cinnamon leaf extract 0.5% can inhibit the growth of bacteria a. hydrophila is characterised by the absence of bacteria that grow on TSA medium.Keywords:   Cinnamomum burmanii, Aeromonas hydrophila,in vitro